Violence Prevention and Control at Hospital - Mishra, Rakesh C. (Journal of Nepal Health Research Council, 2009)
Not uploaded. Key words: Violence; Disoriented; Uncooperative patients DOI: 10.3126/jnhrc.v6i1.2446 Journal of Nepal Health Research Council Vol. 6, No. 1, Issue 12, April, 2008 Page: 58-60